Efeitos da combinação de demonstração, instrução verbal e freqüência de conhecimento de resultados na aquisição de habilidades motoras - Fernando Carneiro Machado Ennes (2004)
Demonstration, verbal instruction and results knowledge are related to the information given throughout the teaching-learning process, and the success in applying them depends not only on the apprentice skill in using such information, but also on the way the teacher presents it. By better understanding the way these variables combination affect Motor Learning, more efficient strategies can be set to the motor skills teaching-learning process, as well as the intervention of the Physical Education professional on the teaching and betterment of skills based on pre-established scientific knowledge. However, these variables combination effects havent been a frequent issue in researches and, therefore, constitutes an important topic to be approached. The current study aimed to corroborate the combination effect of three relative frequencies of result knowledge (33%, 66% and 100%) within three kinds of previous information supply (demonstration, verbal instruction and demonstration added to verbal instruction). The task chosen consisted of a serial skill in ball positioning, in a pre-established sequence to be accomplished at a specific target timing (3.000 ms.). 108 individuals (inexperienced in this task ) ranging from 18 to 35 years of age took part in the experiment. They were picked at random and separated in nine groups (n=12) according to the variables combinations. The experiment consisted of three phases: 60 practice tries in the Acquisition Phase followed by 10 practice tries in the same task on a Retention Test (15 minutes after the Acquisition Phase) and at last, the Transference Test, in a 10 practice tries of a new sequence at a new target timing (2.500 ms.). The accuracy and variability have been measured by the absolute error and standard deviation respectively, under the analysis through an ANOVA two way (groups and blocks), within repeated measures in the second factor for the intergroup comparison in the acquisition phase and another, for the last block in the acquisition phase and tests. In order to obtain the average comparison, a Tukey post hoc test was used. The risk a to the study was set in 5% (p = 0.05). The results found in this study partially corroborate the ones found in previous researches on result knowledge frequency indicating that KR intermediate frequency could lead to higher levels of learning. The results also point out the importance of demonstration to the learning process. The experimental evidences found suggest that intermediate levels of received information, as well as intermediate levels of information processing demands, have presented superior results. It has been concluded that taking for granted the overruled task, the best combinations would be in intermediate points between extreme poles containing either much or little information.